Analisis Etnoparenting Suku Sakai di Era Digital di Desa Bekalar Kecamatan Kandis Kabupaten Siak - Ayu Indah Sundari; Ria Novianti; Defni Satria (Departement of Mathematics Education, 2023)
This study aims to find out how to analyze the ethnoparenting of the Sakai tribe in the digital era by parents to instill local wisdom values ​​of the Sakai culture in Bekalar Village, Kandis District, Siak Regency. The type of research used is descriptive qualitative research. The subjects of this study were 5 parents. The sampling technique used in this study is snowball sampling. Data collection techniques used are through observation, interviews, documentation and triangulation. The results showed that parents applied 5 aspects of parenting based on the book of local wisdom values ​​of Sakai Riau culture, including 1) Human relations with God 2) Human relations with nature 3) Human relations with time 4) Relations with fellow human beings 5) Relationships man with work. Of these 5 aspects, parents have applied them well to their children and 1 other aspect has been implemented quite well. Parents instill the values ​​of the local wisdom of the Sakai culture in their children by advising, giving examples and positive habits. Keywords: Ethnoparenting, Sakai Tribe, Parents